2019
DOI: 10.1177/0194599819856299
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Construct Validity of the Penetration‐Aspiration Scale for Quantifying Pediatric Outcomes after Interarytenoid Augmentation

Abstract: Objective To assess the reliability and construct validity of the Penetration-Aspiration Scale in children. Study Design This was a retrospective cohort study of pre- and postoperative video modified barium swallow studies from children who underwent interarytenoid injection augmentation for unexplained persistent pharyngeal dysphagia. Two pediatric speech and language pathologists reviewed each study twice in a blinded and randomized fashion. Setting Tertiary academic pediatric hospital. Subjects and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…There are inherent limitations on the ability to blind any participants to patient characteristics such as the IAMH noted during surgery by the operating surgeon, and the post‐operative status of patients to the speech and language pathologist during VFSS review. The blinding of surgeons has been considered in previous blinded evaluations of IAAP videos, 14 and in blinded analysis of VFSS samples using the penetration aspiration scale by SLPs 33 ; these concerns will remain worthy of consideration in the interpretation of these data. Of note, we included in our analysis patients whose VFSS were completed over 3 months after their IAIA procedure, although these patients were very limited in number.…”
Section: Discussionmentioning
confidence: 99%
“…There are inherent limitations on the ability to blind any participants to patient characteristics such as the IAMH noted during surgery by the operating surgeon, and the post‐operative status of patients to the speech and language pathologist during VFSS review. The blinding of surgeons has been considered in previous blinded evaluations of IAAP videos, 14 and in blinded analysis of VFSS samples using the penetration aspiration scale by SLPs 33 ; these concerns will remain worthy of consideration in the interpretation of these data. Of note, we included in our analysis patients whose VFSS were completed over 3 months after their IAIA procedure, although these patients were very limited in number.…”
Section: Discussionmentioning
confidence: 99%
“…An SLP of this study collected a medical and developmental history, gave the Pedi -EAT -10, performed a clinical evaluation of dysphagia -bedside swallowing assessment, and evaluated instrumental assessments (FEES or VFSS) [1,[29][30]. During the instrumental assessment, the presence of residue and the penetration and aspiration score via the Penetration / Aspiration Scale (PAS Scale) were measured [24,[31][32]. After all, an interval period of 2 weeks was selected for the second administration of Pedi -EAT -10.…”
Section: Participantsmentioning
confidence: 99%
“…[29] The scale was originally validated in adults by Rosenbek et al, [26] and since then, its reliability and validity are well established so far. [29][30][31] We evaluated airway invasion by liquid material based on PAS scores, ranging from a minimum of 1 point to a maximum of 8 points. In this study, a PAS score within the 6 to 8 range indicated the patient was aspiration-positive, whereas a score in the 1 to 5 range indicated an aspiration-negative status.…”
Section: Subjects and Clinical Evaluationsmentioning
confidence: 99%